Optimising plasmapheresis procedure: The role of plasma unit weight setting. (February 2021) - Marraccini, Chiara; Merolle, Lucia; Giorgi Rossi, Paolo; Baricchi, Roberto; Pertinhez, Thelma A.
Abstract: The AUSL-IRCCS of Reggio Emilia Transfusion Unit operates in two blood donor centers. Plasmapheresis protocols and machines are identical in both centers, except for the final unit weight setting: 700 g in Center 1 and 720 g in Center 2. Within a wider study to assess the anticoagulant content in plasma units through proton nuclear magnetic resonance, we compared the efficiency of the two settings. We analyzed 215 and 100 consecutive samples from Centers 1 and 2, respectively. We collected processed blood volume, net plasma collected and anticoagulant volume in the plasma units. In our experience, setting the machine at 720 g instead of 700 g was associated with a small increase in plasma content of the final unit (only 4 mL), but implied an increase of more than 100 mL of the total processed blood and a higher amount of anticoagulant in the unit. On the contrary, the difference in donor's reinfused anticoagulant was negligible. Our findings come from an observational study suggesting that, in view of a minimal advantage in terms of collected net plasma, there might be relevant disadvantages for the donor in prolonging plasmapheresis over 700 g. Since observed differences may be attributed to confounding factors, we recommend always checking the marginal efficiency of the procedure when the balance target value of the setting is increased. Randomized cross-over studies are needed to find the optimal target weight for plasma units. These studies could also help defining personalized plasmapheresis procedures, thus further optimizing donor safety.